Reposo y germinación de semillas de Enterolobium cyclocarpum (Fabaceae): resultados de un estudio inédito y un experimento fallido - Morales, Carlos O. (Lankesteriana: International Journal on Orchidology, 2016)
S e e d d o r m a n c y a n d g e r m i n a t i o n o f E n t e r o l o b i u m c y c l o c a r p u m ( F a b a c e a e ) : R e s u l t s o f a n unpublished work and an unsuccessful experiment. In Costa Rica, it was determined that in order to reproduce the tree species E. cyclocarpum, selected seeds might weigh 0,7 to 1,0 g. In general, the weighti- est fruits have the greatest mass of viable seeds, so that these fruits might contain the better seeds to be selected. Some seeds of this species germinated after 13 years of dormancy. Now there is evidence that the seeds of a particular crop are predeterminate to germinate in different times, this fact revealing a mid- and long-term advantageous reproductive strategy.